PERBANDINGAN SISTEM PROPORSIONAL TERBUKA DAN SISTEM PROPORSIONAL TERTUTUP DALAM SISTEM PEMILIHAN UMUM DI INDONESIA - Tangko, Lidwina Aprilliana Allo (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2023)
The general election system that will be implemented in 2024 will be a polemic and a debate among political parties. The Judicial Review submitted by several Political Parties to the Constitutional Court, wants a change in the use of the Open Proportional Election System, to a Closed Proportional Election System. This attracts the author to seek a comparison of the Open Proportional Election System and the Closed Proportional Election System. To analyze the Comparison of the Open Proportional System and the Closed Proportional System in the General Election System in Indonesia. The research used is Normative Legal Research. Normative Legal Research is legal research conducted by examining library materials or secondary data. The research was conducted by means of a literature study, which was carried out by tracing, collecting and reviewing data in the form of primary and secondary legal materials related to the research theme, all of which were obtained from the results of literature studies. The data analysis used in this research is qualitative analysis, which is to describe the data in a quality manner in the form of sentences that are organized, sequential, logical, non-overlapping, and effective, so that it can facilitate researchers in analyzing and processing data